2010
DOI: 10.1007/bf03347059
|View full text |Cite
|
Sign up to set email alerts
|

Resistin levelispositively correlated with thrombotic complications in Southern Chinese metabolic syndrome patients

Abstract: In patients with MetS, resistin is strongly associated with hypercoagulative and hypofibrinolitic activities. Moreover, resistin may induce thrombotic complications via mediating the lipoprotein metabolism and stimulating inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Recenty, resistin was shown to induce a procoagulant state in HUVECs by inducing both the expression of tissue factor (TF) and the activity of factor Xa [34]. Correlative observations made in metabolic syndrome cohorts showed that resistin is strongly associated with hypercoagulative and hypofibrinolitic activities [35]. It seems that inflammation-associated increases in the release of resistin into circulation might contribute to the prothrombotic state observed under diabetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recenty, resistin was shown to induce a procoagulant state in HUVECs by inducing both the expression of tissue factor (TF) and the activity of factor Xa [34]. Correlative observations made in metabolic syndrome cohorts showed that resistin is strongly associated with hypercoagulative and hypofibrinolitic activities [35]. It seems that inflammation-associated increases in the release of resistin into circulation might contribute to the prothrombotic state observed under diabetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…108 In chondrocytes, resistin up-regulated several cytokines and chemokines (TNF-a, IL-6, and IL-12), through NF-kB and CCAAT/enhancer-binding protein (C/EBP)b. 109 Moreover, low shear stress modulated resistin-induced COX-2 expression in human OA chondrocytes 110 via NF-kB, cAMP response element binding protein (CREB), AMPK, and SIRT1, indicating the interplay between mechanical shear stress and resistin activity. 110 Mechanical stretch also regulated the resistin expression in vascular smooth muscle cells 111 and cardiomyocytes.…”
Section: Resistinmentioning
confidence: 99%
“…Resistin stimulated osteoblast proliferation and its expression is augmented during osteoclast differentiation, through protein kinase C (PKC) and protein kinase A (PKA) signaling pathways . In chondrocytes, resistin up‐regulated several cytokines and chemokines (TNF‐α, IL‐6, and IL‐12), through NF‐κB and CCAAT/enhancer‐binding protein (C/EBP)β . Moreover, low shear stress modulated resistin‐induced COX‐2 expression in human OA chondrocytes via NF‐κB, cAMP response element binding protein (CREB), AMPK, and SIRT1, indicating the interplay between mechanical shear stress and resistin activity .…”
Section: Resistinmentioning
confidence: 99%
“…In a recent clinical study, the serum resistin level of 90 patients with the MetS was determined and compared with serum levels of mediators of thrombosis (Fang et al ., 2011). It was determined that the average level of resistin in MetS patients with or without acute myocardial or cerebral infarction was significantly higher than that of the control patients.…”
Section: Resistin and Thrombosismentioning
confidence: 99%